Integrating intellectual, emotional, and spiritual intelligence to enhance academic achievement in pencak silat - Rizal, Rony Mohamad; Sobarna, Akhmad; Ediansyah; Alpen, Joni (UIR Press, 2024)
Background Problems: Intellectual, emotional, and spiritual intelligences are believed to influence student learning achievement. However, the specific impact of these intelligences on physical education and, more specifically, on pencak silat learning outcomes remains unexplored. Research Objective: The purpose of this study was to determine the effect of intellectual, emotional, and spiritual intelligence on students' learning achievement in pencak silat. Methods: This research method uses descriptive quantitative causality. We sampled 96 students from a high school in Bekasi City. This study used four instruments: (i) Sternberg triarchic abilities test, (ii) global emotional intelligence test, (iii) spiritual intelligence test, and (iv) pencak silat learning achievement using Bloom's taxonomy. We analysed the data using descriptive statistics, specifically the F-test and T-test. Findings and Results: The study revealed that intellectual, spiritual, and emotional intelligence all play a significant role in enhancing students' learning achievement in pencak silat within physical education settings. Among these, emotional intelligence emerged as the most influential factor, surpassing both intellectual and spiritual intelligence in its impact on academic success. This finding underscores the critical role of emotional regulation and awareness in mastering complex physical and mental skills in pencak silat. Conclusions: The findings highlight the importance of strengthening all aspects of intelligence in education. This research brings a fresh perspective to the field of physical education, highlighting the increasing prominence of emotional intelligence in learning outcomes. It demonstrates the need for the development of emotional intelligence in the context of physical education, particularly in relation to pencak silat. For a more comprehensive understanding, we can conduct further research to investigate the interaction of these intelligences with other variables such as motivation, learning environment, and teaching methods.